Social Achievement Goals in Chinese Undergraduates: Associations With Self-Esteem and Symptoms of Social Anxiety and Depression - Zhao, Yanhua (Frontiers in Psychology, 2022)
The pursuit of relationship goals is critical to the wellbeing of young adults. This study investigated different achievement goals toward social competence as potential predictors of social anxiety and depression symptoms. It proposed that self-esteem may function as a mediator on the pathway from endorsing social achievement goals to undergraduates’ concurrent and longitudinal social anxiety and depression symptoms. Social achievement goal theory proposes three types of goals: social mastery goals (striving to improve one’s social competence), social performance-approach goals (striving to prove one’s social competence and win positive evaluation), and social performance-avoid goals (striving to avoid incompetent social behaviors and negative evaluation). One hundred and eighty-five Chinese undergraduates aged from 18 to 23 (50% female) completed this study across two-time points. Path analyses indicated that social mastery (marginally) and performance-approach goals were positively associated with self-esteem, whereas social performance-avoid goals were negatively associated with self-esteem; self-esteem was negatively associated with the concurrent social anxiety and depression symptoms and the longitudinal depression symptoms. The proposed mediation effects of self-esteem on the links from three types of social achievement goals to the concurrent and longitudinal social anxiety and depression symptoms were significant except on the links from social mastery goals and social performance-approach goals to the subsequent social anxiety symptoms. Self-esteem and the baseline social anxiety and depressive symptoms have a chain mediating effect between social achievement goals and the longitudinal symptoms of social anxiety and depression. These findings suggest that the pursuit of social mastery goals and performance-approach goals in initiating and maintaining social relationships boosts undergraduates’ self-worth and reduces their concurrent and longitudinal depression experiences. However, the strivings to hide inadequacy and avoid negative evaluation in social contexts impede one’s self-worth and increase concurrent and longitudinal social anxiety and depression symptoms. Implications and limitations are discussed.